TOURIST VISIT DECISION MODEL BASED ON COMMUNITY-BASED TOURISM (CBT) AT TOURISM DESTINATIONS - Husni Muharram Ritonga; Dewi Nurmasari Pane; Sienak Krismawati Hia (Universitas Efarina, 2025)
This study aims to analyze the influence of service quality, infrastructure, natural tourism attractions, and facilities on visitors’ decisions to visit Serambi Deli Beach, Deli Serdang Regency, North Sumatra, with Community-Based Tourism (CBT) serving as a moderating variable. This research employs an associative quantitative approach with a total of 71 respondents. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that all four independent variables have a positive and significant effect on visit decisions, both partially and simultaneously. CBT strengthens the influence of service quality, infrastructure, tourism attractions, and facilities on visit decisions. The findings emphasize that enhancing local community participation is crucial for improving the quality of tourism at Serambi Deli Beach.